RSM optimization of microwave pyrolysis parameters to produce OPS char with high yield and large BET surface area. (1st October 2020) - Tripathi, Manoj; Bhatnagar, Ashish; Mubarak, N.M.; Sahu, J.N.; Ganesan, P.
Abstract: Microwave pyrolysis is a very effective technique to convert organic waste into energy rich products. In the present work micro porous and carbonaceous OPS char was synthesized by microwave pyrolysis technique. OPS char yield and its BET surface area was investigated as a function of process parameters to make the microwave pyrolysis of OPS more efficient. Both of these quantities were found to be affected by the process parameters. With the rise in microwave power (MWP) and radiation time (RT), OPS char yield was lowered while increase N2 flow rate (NFR) increased the OPS char yield slightly. Extreme values of either of the process parameter was seen to lower the BET surface area of OPS char. Response Surface Methodology (RSM), was used to optimize the process parameters for maximized OPS char yield and its BET surface area. Regression models for the OPS char yield and its BET surface area were also developed in this study. These regression models were having high Fischer test value & lower p-value which ensure its reliability and applicability. ANOVA analysis of the experimental data provided the process parameters to achieve maximized OPS char yield (60.93%) and BET surface area (250.03 m 2 /g). The predicted results were validated and it was found that the experimental data varied only by 5.99% in yield and 6.34% in BET surface area from the predicted values.